2014
DOI: 10.1016/j.enbuild.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the thermal behaviour of a mortar based brick masonry wall coated with TiO2 nanoparticles: An experimental assessment towards energy efficient buildings

Abstract: The transfer of energy (in the form of heat) between the building and its surroundings affects its thermal performance. When a given building system is thermally inefficient it will require that the HVAC equipment will be in permanent activity, increasing the underlying energy costs. This work evaluates the influence of using a TiO 2-coated plastering mortar in the thermal performance of a building wall model. The TiO 2 aqueous solution was sprayed onto the mortar surface, in its fresh state, by using an atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Temperature ( • C) Structural parameters T TF TF0.5 TF1 TF2 TF5 300 a (Å) 3.7812 (13) 3.7858 (7) 3.7700 (18) 3.7808 (15) (2) 3.7809 (1) 3.7829 (2) 3.7833 (6) 3.7801(6) c (Å) 9.4959(5) 9.4950(4) 9.5015 (6) 9.4973 (20) 9.4838(23) UCV (Å 3 ) 135.62 (2) 135.73 (1) 135.97 (2) 135.94 (7) 135.51(8) D (Å) 302 (6) 368 (14) 337 (9) 245(7) 217 (5) somewhat different from those reported by author authors. Thus, Ganesh et al [42] found small amounts of secondary ␣-Fe 2 O 3 and FeTiO 3 phases in their Fe-doped TiO 2 powders (with Fe content ≥4 wt%) prepared by coprecipitation and thermally treated at 550 • C, while Zhu et al [43] have identified a residual ␣-Fe 2 O 3 phase in their sol-gel TiO 2 powders with iron content ≥5 wt%.…”
Section: Xrdmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature ( • C) Structural parameters T TF TF0.5 TF1 TF2 TF5 300 a (Å) 3.7812 (13) 3.7858 (7) 3.7700 (18) 3.7808 (15) (2) 3.7809 (1) 3.7829 (2) 3.7833 (6) 3.7801(6) c (Å) 9.4959(5) 9.4950(4) 9.5015 (6) 9.4973 (20) 9.4838(23) UCV (Å 3 ) 135.62 (2) 135.73 (1) 135.97 (2) 135.94 (7) 135.51(8) D (Å) 302 (6) 368 (14) 337 (9) 245(7) 217 (5) somewhat different from those reported by author authors. Thus, Ganesh et al [42] found small amounts of secondary ␣-Fe 2 O 3 and FeTiO 3 phases in their Fe-doped TiO 2 powders (with Fe content ≥4 wt%) prepared by coprecipitation and thermally treated at 550 • C, while Zhu et al [43] have identified a residual ␣-Fe 2 O 3 phase in their sol-gel TiO 2 powders with iron content ≥5 wt%.…”
Section: Xrdmentioning
confidence: 99%
“…In search for a photocatalyst with optimal features, titania remains a benchmark against which any alternative photocatalyst must be compared. Enormous studies have been focused to the research of TiO 2 material, which led to many promising applications in different fields, ranging from optics to gas sensors via solar energy [5][6][7][8][9]. These applications can be roughly divided into "energy" and "environmental" categories, many of which depending not only on the properties of the TiO 2 material itself but also on the modifications of the TiO 2 material host and of the interactions of TiO 2 materials with the environment [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic reflection peaks of the initial and modified samples were at eaks is also similar indicating that neither the lattice nor the crystal phase changed after the surface sulfation processes (Fig 2 .). The (110), (101*), (211*) peaks belong to the rutile phase and the (101), ( 103), (004), (200) (211) peaks belong to the anatase phase [31]. XRD pattern for TiO2 (Degussa P25) was assigned by the help ).…”
Section: Characterizationmentioning
confidence: 99%
“…Thermal conduction resistance and thermal transmission co-efficient for the TiO 2 -coated mortar wall were reduced by 10% and 13% respectively. The water evaporation was improved by 136% by coating TiO 2 nanoparticles to mortar wall surface [40]. The thermal property of TiO 2 -paraffin wax composite PCM material was studied by J. Wang et al TiO 2 in Paraffin wax influences the phase change temperature and latent heat capacity of the PCM material.…”
Section: Thermal Comfort In Modern Buildings Using Nano-pcmsmentioning
confidence: 99%